2006
DOI: 10.1063/1.2392674
|View full text |Cite
|
Sign up to set email alerts
|

Charging and discharging processes of carbon nanotubes probed by electrostatic force microscopy

Abstract: Articles you may be interested inUsing an electroconductive carbon nanotube probe tip in scanning nonlinear dielectric microscopy Rev.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 16 publications
2
46
0
Order By: Relevance
“…1͑a͔͒. [12][13][14] After injection, the CNT charge state is then measured by electrostatic force microscopy ͑EFM͒. In this process, the tip is lifted at a distance z Ӎ 100 nm above the sample surface to discard short-range surface forces, and the cantilever resonance frequency shifts are recorded as a probe of electrostatic force gradients acting on the tip biased at a detection voltage V EFM ͓Fig.…”
mentioning
confidence: 99%
“…1͑a͔͒. [12][13][14] After injection, the CNT charge state is then measured by electrostatic force microscopy ͑EFM͒. In this process, the tip is lifted at a distance z Ӎ 100 nm above the sample surface to discard short-range surface forces, and the cantilever resonance frequency shifts are recorded as a probe of electrostatic force gradients acting on the tip biased at a detection voltage V EFM ͓Fig.…”
mentioning
confidence: 99%
“…Confirming Maxwell's pioneering results (Maxwell, 1878), experiments have shown that the charge distribution along a CNT subjected to an electric field is generally non uniform along the length, with evident end enhancements (Zdrojek et al, 2005(Zdrojek et al, , 2006Wang et al, 2008). The available experimental tests concern micron-long CNTs.…”
Section: Introductionmentioning
confidence: 67%
“…More recently, Griffith and Li (1996) and Jackson (2000) computed semi-analytic expressions of the charge density distribution in qualitative agreement with Maxwell's solution. Experimental tests proving charge end enhancements were carried out by Zdrojek et al (2005Zdrojek et al ( , 2006 and Wang et al (2008). These authors investigated the electrostatic properties of single-separated MWCNTs and single-walled CNTs deposited on a dielectric layer by charge injection and electric force microscopy experiments.…”
Section: Charge End Enhancementsmentioning
confidence: 99%
“…[6][7][8] EFM has also been used to inject charge and study its distribution in various types of samples, such as Co and Si nanoclusters embedded in conductive 9 and non-conductive substrates, 10,11 semiconductor nanoparticles, 12 oxide 13,14 and alumina films, 15 quantum dots, 16,17 and carbon nanotubes. 18,19 Briefly, EFM is a dual pass technique: in the first line scan the tip operates in tapping mode, acquiring a topography profile of the sample surface. In the second line scan (interleave), the topographic data are used to retrace the first scan while the tip travels at a defined height above the surface.…”
mentioning
confidence: 99%